MRI Feature Tracking Strain in Pulmonary Hypertension: Utility of Combined Left Atrial Volumetric and Deformation Assessment in Distinguishing Post- From Pre-capillary Physiology - Leong, Kai'En; Howard, Luke; Lo Giudice, Francesco; Pavey, Holly; Davies, Rachel; Haji, Gulammehdi; Gibbs, Simon; Gopalan, Deepa (Frontiers in Cardiovascular Medicine, 2022)
Aims Pulmonary hypertension (PH) is dichotomized into pre- and post-capillary physiology by invasive catheterization. Imaging, particularly strain assessment, may aid in classification and be helpful with ambiguous haemodynamics. We sought to define cardiac MRI (CMR) feature tracking biatrial peak reservoir and biventricular peak systolic strain in pre- and post-capillary PH and examine the performance of peak left atrial strain in distinguishing the 2 groups compared to TTE. Methods and results Retrospective cross-sectional study from 1 Jan 2015 to 31 Dec 2020; 48 patients (22 pre- and 26 post-capillary) were included with contemporaneous TTE, CMR and catheterization. Mean pulmonary artery pressures were higher in the pre-capillary cohort (55 + 14 mmHg vs 42 + 9 mmHg; p<0.001) as was pulmonary vascular resistance (median 11.7 WU vs 3.7 WU; p<0.001). Post-capillary patients had significantly larger left atria (60 + 22 ml/m2 vs 25 + 9 ml/m2; p<0.001). There was no difference in right atrial volumes between groups (60 + 21 ml/m2 vs 61 + 29 ml/m2; p=0.694), however peak RA strain was lower in post-capillary PH patients (8.9 + 5.5% vs 18.8 + 7.0%; p<0.001). In the post-capillary group, there was commensurately severe peak strain impairment in both atria (LA strain 9.0 + 5.8%, RA strain 8.9 + 5.5%). CMR LAVi and peak LA strain had a multivariate AUC of 0.98 (95% CI 0.89-1.00; p<0.001) for post-capillary PH diagnosis which was superior to TTE. Conclusion CMR volumetric and deformation assessment of the left atrium can highly accurately distinguish post- from pre-capillary PH.